Studi Unjuk Kerja Smart Microgrid Sistem Hibrid di Jurusan Teknik Elektro Universitas Udayana Kampus Bukit Jimbaran - Arsikaputra, I Putu; Giriantari, I.A.D.; Ariastina, W.G. (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— Most of the power plants use fossil energy sources, while fossil energy has several undesirable effects. To overcome this, it is necessary to develop in electricity that is by using renewable energy as a source of electrical energy. Some examples of electrical renewable energy sources used are solar energy and wind energy. Renewable energy as electricity generation can be developed using a microgrid concept, generation with more than one power plant. The combination of different types of power plants is often called a hybrid power plant. One example is a hybrid power plant with a smart microgrid network system at the Department of Electrical Engineering, Faculty of Engineering, Udayana University, which has been operating since 2017, which is a collaboration between Udayana University and the Ministry of Energy and Mineral Resources (ESDM). This smart microgrid requires a study of the energy supply system of the power generation in order to know its performance to serve the DH building load. The study will analyze the data in October 2018. Research results show that smart microgrids cannot fully meet the electricity load in October 2018. The electrical energy load of 4330 kWh DH building is supplied by PLTS 333,383 kWh, PLTB 121.07 kWh, and supply of 803.57 batteries. kWh The shortage of electrical energy from the microgrid system is supplied by PLN by 1591.7 kWh and when overproduction, PLN can get energy from the 541 kWh microgrid. Battery charging energy is 1894.38 kWh. The use of renewable energy in the DH building reached 63.24%.  Keywords— Microgrid, PLTS, PLTB, Battery